Gene therapy randomised clinical trials in Europe – a review paper of methodology and design. Issue 1 (1st January 2020) - Ilieva, Krassimira; Borissov, Borislav; Toumi, Mondher
ABSTRACT: Purpose : Gene therapy brings opportunities to discover cures for diseases for which there are no adequate treatments. As most gene therapies target rare diseases, several challenges are associated with their clinical development, such as limited population size, lack of established clinical pathways for development, and sometimes the absence of validated endpoints. The objective of this study was to systematically review and evaluate the methodology and design of European clinical trials (CTs) utilising gene therapy medicinal products (GTMPs). Methods : A systematic search of online CT databases was performed using keywords to identify CTs conducted with GTMPs in Europe, published from 1 January 1995 to 31 July 2019. Results : The search identified 1571 CTs, of which 199 were identified as published articles. A total of 159 CTs remained following the elimination of duplicated CTs, non-gene therapy trials, and those conducted outside Europe. Of these, only nine CTs were randomised, double-blind, with or without parallel groups, and placebo-controlled. Conclusions : The analysed randomised CTs were conducted in accordance with Good clinical practice with low risk of bias across domains. Only one CT was identified with some concerns of bias due to lack of information regarding the randomisation process and changes in protocol.